Impact of psoriasis on mortality rate and outcome in myocardial infarction - Karbach, Susanne; Keller, Karsten (Journal of the American Heart Association, 2020)
Psoriasis is a frequent chronic inflammatory cytokine‐mediated skin disease and was identified to be an independent risk factor for the occurrence of myocardial infarction (MI). However, data about the impact of psoriasis on mortality and other in‐hospital adverse events in the setting of MI are sparse and inconsistent.Methods and ResultsThe nationwide German inpatient sample of the years 2005 to 2016 was used for statistical analysis. Hospitalized patients with MI were stratified for the presence of psoriasis and the impact of psoriasis on in‐hospital events was investigated. Overall, 3 307 703 patients with MI (37.6% females, 56.8% aged ≥70 years) were treated in Germany (2005-2016); among them 9028 (0.3%) were diagnosed with psoriasis. Patients with MI with psoriasis were significantly younger (68.0 [58.0-76.0] versus 73.0 [62.0-81.0] years; P<0.001) and showed significant lower in‐hospital case‐fatality rate (7.1% versus 12.4%; P<0.001), confirmed in the regression (odds ratio, 0.68; 95% CI, 0.63-0.74; P<0.001) adjusted for age, sex, and comorbidities. They more frequently revealed cardiovascular risk factors such as arterial hypertension (58.9% versus 55.0%; P<0.001), hyperlipidemia (44.4% versus 38.6%; P<0.001), smoking (14.3% versus 7.4%; P<0.001), diabetes mellitus (34.8% versus 30.4%; P<0.001) or obesity (17.9% versus 9.3%; P<0.001). While the rate of percutaneous coronary intervention (41.4 versus 42.0%; P=0.223) was comparable between both groups, coronary bypass surgery was more often performed in patients with MI with psoriasis (7.7% versus 4.7%; P<0.001).ConclusionsOverall, only 0.3% of all MI cases were diagnosed with psoriasis, and patients with MI with psoriasis were in median 5 years younger than patients with MI without psoriasis. Psoriasis seems to enhance the prevalence of classical cardiovascular risk factors and might therefore explain the earlier time point for MI. Our data also showed in turn a lower in‐hospital mortality rate in patients with MI with psoriasis, presumably driven by younger age.
Gesehen am 17.11.2020